Analysis of Stress and Pillar Strength in Underground Coal Mines - Ilep Prengki; Barlian Dwinagara; S Koesnaryo; Singgih Saptono; Eddy Winarno (Science and Environmental Journal for Postgraduate, 2023)
Underground coal mining is located in Tanah Kuning, Batu Tanjung Village, Talawi District, Sawahlunto City. Some constraints arose in a CV. BMK is the existence of several mining fronts on mining blocks that have started to become critical and fail. It can be seen from the condition of the supports in some places that they have started to crook and break. In addition, in several locations, many rocks were found hanging (wedges) on the roof of the openings that could be seen between the rows of supports. This indicates a significant change in strain around the coal pits and pillars. The research was carried out by testing in situ stresses using Flat-jack, observing the condition of the rock mass, and testing the physical and mechanical properties of the rock. The purpose of this study was to find out the magnitude of the strength and stress on the pillarbased on the theory of tributary area loading, to provide safe and economical pillar geometry recommendations, and to discover the causes of rock mass movements. Based on the results of the analysis using the Tributary Area theory, the Safety factor Pillar 1 obtained was categorized as unsafe based on the reference value of the safety factor. The most ideal pillar size recommendation based on previous geotechnical studies was 9 m x 9 m with a maximum recovery of 38% and a safety factor of 1.7. Based on the results of the calculation of strength and loading on the pillars, the value of Pillar 1 strength is 6.0 MPa, Pillar 2 strength was 9.57 MPa, and Pillar 3 was 10.9 MPa with the value of Pillar load for Pillar 1 = 5.1 MPa, Pillar 2 = 4.47 MPa and Pillar 3 = 5.58 Mpa.